Association of Dental Caries Based on Frequency of Tooth Brushing Habit - A Retrospective Study - A, BAALA VIGNESH.; P, JESSY.; JAIN, RAVINDRA KUMAR (The journal of contemporary issues in business and government, 2021)
Background: Tooth brushing is one of the fundamental self-care behaviors seen in an individual. It is important for one’s oral health and its maintenance. Dental caries is an infectious disease that damages tooth structure and causes cavities. Aim: The aim of this study is to evaluate the association of dental caries based on the frequency of tooth brushing in individuals. Materials and method: Data was collected retrospectively from the dental records of patients visiting saveetha dental college. Patient gender, carious tooth, frequency of brushing and toothpaste used was collected by reviewing the case sheets. The obtained data was entered in MS excel spreadsheet and imported to spss for statistical analysis. Chi square test was applied and level of significance was set p<0.05. Result: The results proved that 76.1% of the individuals brushed once daily and 23.9% of the individuals brushed twice a day .The prevalence of usage of fluoride containing toothpaste was 46.8% .There was a significant association between frequency of tooth brushing habit and DMFT score (p<0.05) .Individuals who had brushed twice a day with fluoride containing toothpaste , showed lesser DMFT scores indicating the decreased incidence of dental caries. Conclusion: Within the limits of the study, it can be concluded that individuals with the lesser frequency of brushing habit and using non-fluoridated toothpaste had increased DMFT scores.